Guanosine-based hydrogen-bonded 2D scaffolds: Metal-free formation of G-quartet and G-ribbon architectures at the solid/liquid interface - El Garah, Mohamed; Perone, Rosaria C.; Bonilla, Alejandro Santana; Haar, Sebastien; Campitiello, Marilena; Gutierrez, Rafael; Cuniberti, Gianaurelio (Giovanni); Masiero, Stefano; Ciesielski, Artur; Samori, Paolo (Chemical Communications, 2015)
We report on the synthesis and self-assembly of three novel lipophilic guanosine derivatives exposing a ferrocene moiety in the C(5′) position of the sugar unit. Their self-association in solution, and at the solid/liquid interface, can be tuned by varying the size and nature of the C(8)-substituent, leading to the generation of either G-ribbons, lamellar G-dimer based arrays or the G4 cation-free architectures.
CRIS-Team Scopus Importer:2023-03-20